Co-ordination of technological bays of sugar refinery operation with provision of forecasting problems - Ladaniuk, A. P.; Zaiets, N. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Problem of unification of coordination procedure for technological complexes on the example of technological complex sugar refinery is considered. The method of decision making using fuzzy logis is suggested. The method is aimed at coordination of decisions by levels in multilevel hierarchial system